Case series of progressive familial intrahepatic cholestasis type 3: Characterization of variants in ABCB4 in China - Cheng, Jinlin; Gong, Ling; Mi, Xiaoxiao; Wu, Xiangyan; Zheng, Jun; Yang, Wenjun (Frontiers in Medicine, 2022)
Objective To improve the accuracy of the diagnosis of familial progressive intrahepatic cholestasis type 3 (PFIC3, https://www.omim.org/entry/602347). Materials and methods Between September 2019 and March 2021, we recruited four patients with PFIC3 from two liver centers in East China. Molecular genetic findings of ATP-binding cassette subfamily B member 4 [ATP binding cassette transporter A4 (ABCB4), https://www.omim.org/entry/171060] were prospectively examined, and clinical records, laboratory readouts, and macroscopic and microscopic appearances of the liver were analyzed. Results Four patients experienced cholestasis, mild jaundice, and elevated levels of serum direct bilirubin, γ-glutamyltransferase, or total bile acids. All patients had moderate-to-severe liver fibrosis or biliary cirrhosis, and their liver biopsy specimens stained positive with rhodamine. Molecular immunohistochemistry revealed reduced or absent MDR3 expression in all liver specimens. A novel mutation of ABCB4 (c.1560 + 2T > A) was identified in patients with PFIC3, which is of high clinical significance and may help understand mutant ABCB4 pathogenesis. Conclusion MDR3 immunohistochemistry and molecular genetic analyses of ABCB4 are essential for the accurate diagnosis of PFIC3.